Between germany and the tropics, between modernity and classicism. leopold rother's work in colombia (2004)
Nazism in Gennany, the Spanish Civil War, and other causes of forced exiles contributed significantly to the intellectual vitality and creativeness of the Americas. Few of these European exiles arrived in Colombia, but those who did were very talented. Leopoldo Rother was one of them. He carne to Colombia in 1936, the same year the Escuela de Arquitectura de la Universidad Nacional de Colombia (National University of Colombia's School of Architecture) was founded. He shared his knowledge of arts and music, a tireless working ability and  above all a great dexterity in the handling of architectural languages that oscillated between classicism and modernism. All his accomplishments were of high quality. In this article I present twelve of this projects, of which the building of the Imprenta de la Universidad Nacional en Bogotá (Printing Press of the National University in Bogotá) eloquently illustrates his sense of classical modulation and sensitivity to detail. In addition it shows his resourceful use of architectural shells and concrete columns, open floor space, changing lights and contemporary use of space.